BRD4 regulates self‐renewal ability and tumorigenicity of glioma‐initiating cells by enrichment in the Notch1 promoter region. Issue 6 (4th October 2020) - Tao, Zhennan; Li, Xuetao; Wang, Hao; Chen, Guangliang; Feng, Zibin; Wu, Yue; Yin, Haoran; Zhao, Guozheng; Deng, Zhitong; Zhao, Chaohui; Li, Yanyan; Sun, Ting; et al.
Abstract: Bromodomain and extraterminal domain (BET) family proteins are considered to be epigenetic readers that regulate gene expression by recognizing acetyl lysine residues on histones and nonhistone chromatin factors and have been classified as curative targets for a variety of cancers. Glioma‐initiating cells (GICs), which commit self‐renewal, perpetual proliferation, multidirectional differentiation, and vigorous tumorigenicity, sustain the peculiar genetic and epigenetic diversification in the GBM patients, thus, GICs result in tumor recurrence. Abundant evidence demonstrates that BET proteins regulate differentiation of stem cells. However, it endures ambiguous how individual BET proteins take part in GIC advancement, and how do small molecule inhibitors like I‐BET151 target functional autonomous BET proteins. Here, we validated that BRD4, not BRD2 or BRD3, has value in targeted glioma therapy. We announce a signaling pathway concerning BRD4 and Notch1 that sustains the self‐renewal of GICs. Moreover, in‐depth mechanistic research showed that BRD4 was concentrated at the promoter region of Notch1 and may be involved in the process of tumor metabolism. Furthermore, in intracranial models, I‐BET151 eliminated U87 GICs' tumorigenicity. The outcomes of this research could be conducive to design clinical trials for treatment of glioma based on BRD4. Abstract : 1. We evaluated BRD4, not BRD2 or BRD3, has value in targeted glioma therapy. 2. A signaling pathway involving BRD4 and Notch1 sustains GICs' self‐renewal. 3. BRD4 was enriched at Notch1 promoter region and may be involved in the process of tumor metabolism. 4. BRD4 abolished the tumorigenicity of GICs in intracranial model after I‐BET151 (BET inhibitor) treatment.